Antibacterial and Proliferative Effects of NaOH-Coated Titanium, Zirconia, and Ceramic-Reinforced PEEK Dental Composites on Bone Marrow Mesenchymal Stem Cells - Artiom Lijnev; Jeevithan Elango; Vicente M. Gómez-López; Carlos Pérez-Albacete Martínez; José Manuel Granero Marín; José Eduardo Maté Sánchez De Val (MDPI AG, 2022)
Several metallic and polymer-based implants have been fabricated for orthopedic applications. For instance, titanium (Ti), zirconia (Zr), and polyetheretherketone (PEEK) are employed due to their excellent biocompatibility properties. Hence, the present study aimed to compare the functional and biological properties of these three biomaterials with surface modification. For this purpose, Ti, Zr, and ceramic-reinforced PEEK (CrPEEK) were coated with NaOH and tested for the biological response. Our results showed that the surface modification of these biomaterials significantly improved the water contact, protein adhesion, and bioactivity compared with uncoated samples. Among the NaOH-coated biomaterials, Ti and CrPEEK showed higher protein absorption than Zr. However, the mineral binding ability was higher in CrPEEK than in the other two biomaterials. Although the coating improved the functional properties, NaOH coating did not influence the antibacterial effect against E. coli and S. aureus in these biomaterials. Similar to the antibacterial effects, the NaOH coating did not contribute any significant changes in cell proliferation and cell loading, and CrPEEK showed better biocompatibility among the biomaterials. Therefore, this study concluded that the surface modification of biomaterials could potentially improve the functional properties but not the antibacterial and biocompatibility, and CrPEEK could be an alternative material to Ti and Zr with desirable qualities in orthopedic applications.